Spherical boron nitride particles and methods for making the same

CN122940463APending Publication Date: 2026-10-20FUJIAN ZHENJING NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611425785.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-15
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0006]针对现有球形氮化硼制备技术中存在的粘结剂残留碳导致B4C杂质相生成、烧结助剂以第二相形式永久残留在晶界处增加界面热阻的问题,本发明提供了一种球形氮化硼颗粒的制备方法,通过粘结剂与烧结助剂的“双零残留”设计及配套工艺优化,实现了高纯度、高导热球形氮化硼的制备

Benefits of technology

1、粘结剂基本上“零残留”:彻底消除碳污染源。本发明采用聚碳酸亚丙酯(PPC)或聚乙二醇(PEG)作为粘结剂,替代传统的聚乙烯醇缩丁醛(PVB)。PPC在惰性气氛下通过“解拉链”机制完全分解为CO2和H2O,灰分残留低于10ppm;PEG热分解同样清洁彻底、无残留。从根源上消除了碳残留及B4C杂质相的生成,保证了氮化硼晶体结构的完整性和晶界的纯净度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses spherical boron nitride particles and their preparation method. The method includes: mixing hexagonal boron nitride powder, a binder, a dispersant, a sintering aid, and a solvent to prepare a slurry; drying the slurry by spray granulation to obtain spherical precursor particles; and debinding and sintering the spherical precursor particles to obtain spherical boron nitride particles. The binder is selected from at least one of polypropylene carbonate and polyethylene glycol, and the sintering aid is a mixture of boron oxide and carbonaceous additives or a borate ester compound. This invention, through the design of a binder with no carbon residue and a sintering aid with no second-phase residue, eliminates carbon pollution sources and interfacial thermal resistance at the source. The resulting spherical boron nitride particles have a carbon residue of less than 0.01 wt% and no second-phase residue at the grain boundaries, significantly improving thermal conductivity and making them suitable for thermal interface materials, thermal conductive gels, thermal conductive pads, and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of inorganic non-metallic materials and thermally conductive fillers, specifically relating to a method for preparing spherical hexagonal boron nitride particles. Background Technology

[0002] Hexagonal boron nitride (h-BN) is an ideal filler for high-end thermal interface materials due to its intrinsically high thermal conductivity (theoretically up to 400 W / m·K), excellent electrical insulation, and thermal stability. However, commercially available h-BN powders are mostly two-dimensional flakes, which are easily preferentially oriented along the flow direction under the influence of shear force during polymer molding. This is beneficial for internal thermal conductivity, but the thermal conductivity in the vertical direction is low, becoming a bottleneck for heat dissipation. At the same time, the large specific surface area of ​​the flake filler leads to a sharp increase in the viscosity of the system during filling, limiting the maximum filler content and severely restricting the overall thermal conductivity of the composite material. Sphericalizing boron nitride is one of the effective ways to overcome the above difficulties. Ideal spherical h-BN particles have isotropic thermal conductivity, which can reduce orientation dependence; their ball effect and low specific surface area can significantly reduce the viscosity of the system, achieving high volume fraction filling and building a dense thermally conductive network; and their high packing density is conducive to efficient point-to-point heat transfer.

[0003] Currently, the main method for preparing spherical boron nitride is spray granulation. This involves first preparing a slurry of hexagonal boron nitride with binders, dispersants, sintering aids, and solvents, then spray granulating it to obtain spherical precursor particles, followed by debinding and sintering to obtain the final spherical boron nitride product. However, existing technologies still face two core challenges: Firstly, residual carbon in the binder disrupts the crystal structure. Current technologies widely use polyvinyl butyral (PVB) as a binder. During the binder removal process, especially during thermal decomposition under an inert atmosphere, PVB produces carbonaceous residues. Studies have shown that PVB degrades in a nitrogen atmosphere to form carbon black. This residual carbon reacts with boron nitride during subsequent high-temperature sintering to form B4C impurity phases, disrupting the crystal structure of boron nitride. Simultaneously, it remains at grain boundaries, becoming phonon scattering centers and severely reducing thermal conductivity.

[0004] Secondly, sintering aids remain permanently at the grain boundaries as a second phase. Current technologies typically use oxides such as Al2O3 and Y2O3 as sintering aids. While these aids promote densification, the thermal conductivity of Al2O3 is only about 30 W / m·K, and that of Y2O3 is only about 15 W / m·K, far lower than the theoretical value of 400 W / m·K for hexagonal boron nitride. This constitutes a significant source of interfacial thermal resistance, severely limiting further improvements in thermal conductivity.

[0005] The information disclosed in this background section is only for enhancing the understanding of the background technology of the present invention, and therefore may include information that does not constitute prior art. Summary of the Invention

[0006] To address the problems in existing spherical boron nitride preparation techniques, such as the formation of B4C impurity phase due to residual carbon in the binder and the permanent residue of sintering aids at grain boundaries in the form of a second phase, which increases interfacial thermal resistance, this invention provides a method for preparing spherical boron nitride particles. Through a "double zero residue" design for both binder and sintering aids and optimization of the supporting process, high-purity, high-thermal-conductivity spherical boron nitride is prepared.

[0007] However, the present invention is not limited to the above aspects, but can be extended in various ways without departing from the technical spirit of the present invention.

[0008] One aspect of the present invention provides a method for preparing spherical boron nitride particles, the method comprising the following steps: Step S1, mixing hexagonal boron nitride powder, binder, dispersant, sintering aid and solvent to prepare a slurry; Step S2, drying and molding the slurry by spray granulation to obtain spherical precursor particles; Step S3, debinding and sintering the spherical precursor particles to obtain spherical boron nitride particles; wherein the binder is selected from at least one of polypropylene carbonate and polyethylene glycol, and the sintering aid is a mixture of boron oxide and carbonaceous additives or a borate ester compound.

[0009] In an embodiment of the present invention, the slurry further contains 0.5-2% nano-oxide powder relative to the mass of the binder, wherein the nano-oxide is selected from at least one of nano CeO2 and nano MnO2.

[0010] In an embodiment of the present invention, the sintering aid is a mixture of boron oxide and carbonaceous additives, wherein the carbonaceous additives are selected from at least one of carbon black and graphite, and the amount of carbonaceous additives added is 5-20% of the mass of boron oxide.

[0011] In embodiments of the present invention, the sintering aid is a borate ester compound, wherein the borate ester compound is selected from at least one of trimethyl borate and triethyl borate.

[0012] In an embodiment of the present invention, the adhesive removal adopts a segmented temperature-controlled adhesive removal process: the temperature is increased at a rate of 0.2-0.5℃ / min in the main decomposition temperature range of the adhesive, and at least one heat preservation platform is set in the main decomposition temperature range, and the heat preservation time of the heat preservation platform is 1-4h.

[0013] In an embodiment of the present invention, during the heat preservation platform stage, a vacuuming and protective gas filling operation is performed every 15-45 minutes.

[0014] In an embodiment of the present invention, the sintering adopts a two-step sintering process: first, the temperature is raised to 1350-1450℃ at a rate of 4-6℃ / min and held for 1.5-3h, and then raised to 1950-2050℃ at a rate of 2-4℃ / min and held for 2-4h.

[0015] In an embodiment of the present invention, after the second heat treatment step of sintering is completed, the temperature is maintained at 1950-2050°C for 20-60 minutes while a protective gas is purged.

[0016] In an embodiment of the present invention, the process conditions for spray granulation are as follows: inlet temperature 150-190℃, outlet temperature 90-110℃, liquid inlet rate 3.5-5.5L / h, and centrifugal atomizing disc motor frequency 120-180Hz.

[0017] Another aspect of the present invention provides spherical boron nitride particles, which are prepared by the above-described preparation method.

[0018] Compared with the prior art, the beneficial effects of the present invention may include: 1. The binder is virtually "zero residue": completely eliminating the source of carbon pollution. This invention uses polypropylene carbonate (PPC) or polyethylene glycol (PEG) as a binder, replacing the traditional polyvinyl butyral (PVB). PPC completely decomposes into CO2 and H2O under an inert atmosphere through a "zipper unzipping" mechanism, with ash residue below 10 ppm; PEG thermal decomposition is equally clean and thorough, leaving no residue. This eliminates carbon residue and the formation of B4C impurity phases at the source, ensuring the integrity of the boron nitride crystal structure and the purity of the grain boundaries.

[0019] 2. Sintering aids are virtually "zero-residue": eliminating interfacial thermal resistance. This invention employs a synergistic system of boron oxide (B2O3) and carbonaceous additives, or uses borate ester precursors. B2O3 is converted into gaseous products at high temperature through a carbothermic reduction reaction, and the B atoms of the conversion product can dissolve into the adjacent boron nitride lattice to repair boron vacancy defects. During the binder removal process, the borate ester precursor undergoes in-situ hydrolysis to generate B2O3, achieving uniform dispersion at the molecular level, reducing the required addition amount by 30-50%. After completing its densification function, the sintering aid is completely discharged in gaseous form, leaving no second phase residue at grain boundaries.

[0020] 3. Process Adaptation for Adhesive Characteristics: Segmented Temperature-Controlled Adhesive Removal. Addressing the "zipper-like" decomposition mechanism of PPC (decomposition occurs in steps, with the main decomposition range being 250-400℃), this invention employs a segmented temperature-controlled adhesive removal process. Within the main decomposition temperature range, the temperature is increased at an extremely slow rate (0.2-0.5℃ / min), with long-term heat preservation platforms (1-4 hours) set at 300℃ and 380℃. This ensures that each decomposition stage is fully completed, allowing sufficient time for decomposition products to diffuse and escape, preventing the accumulation of residual carbon on the particle surface.

[0021] 4. Enhancement measures for the glue removal process: Pulsed atmosphere disturbance. During the glue removal and heat preservation platform stage, a pulsed atmosphere disturbance cycle of vacuuming and protective gas filling is performed every 15-45 minutes. The periodic changes in gas pressure force the gaseous products generated by decomposition out of the particles from the inside and surface, further reducing the risk of residual carbon.

[0022] 5. Process adaptation for sintering aid characteristics: Carbothermic reduction and high-temperature venting. For the synergistic system of B2O3 + carbonaceous additives, the carbothermic reduction reaction is triggered during the holding stage at 1350-1450℃; after holding at 1950-2050℃, the temperature is maintained for another 20-60 minutes while maintaining protective gas purging to ensure the full removal of reaction products CO / CO2 and residual B2O3. For borate ester precursors, their in-situ hydrolysis characteristics during the debinding and heating process are utilized to ensure that the generated B2O3 is uniformly dispersed at the grain boundaries of each boron nitride particle in a molecular-level state, significantly improving sintering efficiency.

[0023] 6. Excellent comprehensive performance. The spherical boron nitride particles obtained by this invention have a carbon residue of less than 0.01 wt%, no second phase residue at the grain boundaries, and a thermal conductivity of up to 7.4 W / m·K when compounded with thermally conductive composite powder and silicone oil. Attached Figure Description

[0024] The accompanying drawings, which are incorporated in and constitute a part of this specification, are included to provide further explanation of the invention. The drawings illustrate exemplary embodiments of the invention and, together with the description, serve to explain the principles of the invention.

[0025] Figure 1 This is a scanning electron microscope (SEM) image of spherical boron nitride particles according to an embodiment of the present invention.

[0026] Figure 2 This is an X-ray diffraction (XRD) pattern of spherical boron nitride particles according to Example 1 of the present invention.

[0027] Figure 3 The image shows the XRD pattern of spherical boron nitride particles according to Comparative Example 1 of the present invention.

[0028] Figure 4The image shows the XRD pattern of spherical boron nitride particles according to Comparative Example 2 of the present invention. Detailed Implementation

[0029] The present invention will be further described in detail below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. After reading the contents of this invention, those skilled in the art can make various alterations or modifications to the present invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0030] In the specific embodiments of this invention, unless otherwise stated, all chemical raw materials used are conventional commercially available reagents. Various auxiliaries, fillers, catalysts, etc., involved can be obtained through commercial channels or prepared according to methods known in the art. The equipment used in this invention is all conventional equipment in the art; its model and specifications do not affect the implementation of the technical solution of this invention, and those skilled in the art can make reasonable selections according to actual production scale and process requirements.

[0031] For inventions involving chemical compositions, the content of each component in the specific embodiments is expressed in parts by weight, weight percentage, or molar ratio, and the specific expression method is determined according to the properties of the composition and the conventions of the relevant technical field. The selection of the content range of each component is based on its influence on the final material properties, and the technical effects of the present invention can be achieved within the scope disclosed in this invention. Those skilled in the art should understand that both the endpoint values ​​and intermediate values ​​of the content of each component can achieve the purpose of the present invention, and the specific values ​​can be adjusted according to actual needs.

[0032] In the preparation method of this invention, the operating temperature, time, pressure, pH value, stirring speed, and other process parameters of each process step are all within the conventional range in the art. Those skilled in the art can optimize and select within the above range according to the actual equipment conditions and raw material characteristics. It should be understood that the range of process parameters disclosed in this invention includes endpoint values ​​and any values ​​between endpoint values. These values ​​can all achieve the technical effects of this invention and are all within the protection scope of this invention.

[0033] The following will describe in detail the alumina-filled boron nitride composite particles and their preparation method of the present invention.

[0034] In the following description, the theoretical basis of spherical boron nitride particles and their preparation methods according to some embodiments of the present invention may be involved. It is understood that these theoretical basis are only for the purpose of understanding the present invention and are not intended to limit the present invention in any way. That is, the effects of the spherical boron nitride particles and their preparation methods of the present invention are not limited by these theoretical basis; that is, they may be based on other theoretical basis besides these theoretical basis.

[0035] One aspect of the present invention provides a method for preparing spherical boron nitride particles. The specific steps of this preparation method are described below.

[0036] The preparation method of spherical boron nitride particles of the present invention includes three core steps: Step S1: Slurry preparation—mixing hexagonal boron nitride powder, binder, dispersant, sintering aid and solvent to prepare slurry; Step S2: Spray granulation—drying and shaping the slurry by spray granulation to obtain spherical precursor particles; Step S3: Heat treatment—debinding and sintering the spherical precursor particles to obtain spherical boron nitride particles.

[0037] The core difference between this invention and existing technologies lies in its "double zero residue" design, meaning that neither the binder nor the sintering aid remains substantially in the spherical boron nitride particles after use. To achieve this design, this invention not only employs special binders and sintering aids in its material selection, but more importantly, it specifically adapts and optimizes the process steps and parameters based on the physicochemical properties of these special substances. The invention will be described in detail below from the perspectives of the binder system and the sintering aid system.

[0038] Selection of adhesive system and its supporting processes Adhesive selection In traditional processes for preparing spherical boron nitride, polyvinyl butyral (PVB) is widely used as a binder. PVB's molecular structure contains numerous carbon-carbon backbones and side groups. When heated in an inert atmosphere (such as N2), these carbon chains cannot be oxidized but only partially decompose, ultimately leaving carbonaceous residues. Studies have shown that PVB degrades in a nitrogen atmosphere to form carbon black. These residual carbons react with boron nitride during subsequent high-temperature sintering at 2000℃ to form the B4C impurity phase, disrupting the crystal structure of boron nitride.

[0039] This invention uses polypropylene carbonate (PPC) or polyethylene glycol (PEG) as a binder. Taking PPC as an example, its molecular chain contains carbonate bonds (-O-CO-O-), which break down through a "chain breaking" mechanism when heated, producing CO2 and H2O as decomposition products. This decomposition process is a thermal decomposition reaction that does not depend on oxygen, and therefore can be completely decomposed under an inert atmosphere. QPAC ® The series of PPC adhesives can be completely decomposed in air, oxygen, nitrogen, hydrogen, argon, and vacuum, with ash residue below 10 ppm (i.e., <0.001 wt%). The thermal decomposition of PEG is also clean and thorough; studies have shown that PEG adhesives can be completely degraded without residue formation.

[0040] Another significant advantage of PPC over PVB is its lower decomposition temperature—PPC's thermal decomposition temperature is nearly 200°C lower than PVB's, which can effectively reduce the adhesive discharge temperature and reduce the thermal shock to the boron nitride particle structure.

[0041] Based on the above characteristics, this invention selects PPC or PEG as the binder, laying the foundation for achieving "zero carbon residue" at the material level. However, simply changing the binder material is insufficient—the "zipper-unzipping" decomposition of PPC is not completed instantaneously at a single temperature, but rather occurs stepwise over a wide temperature range. If the debinding process is not adapted to this decomposition characteristic, incomplete decomposition or accumulation of decomposition products on the particle surface may still occur. Therefore, this invention further incorporates the following targeted improvements at the process level.

[0042] Supporting process improvement 1: Segmented temperature-controlled glue discharge The thermal decomposition of PPC occurs in steps: at lower temperatures (approximately 150-250°C), intermediate products such as cyclic propylene carbonate are formed under the action of residual catalysts; at higher temperatures (approximately 250-400°C), the molecular chains break further, ultimately decomposing completely into CO2 and H2O. The 250-400°C range is the main decomposition temperature range for PPC, within which the decomposition rate is fastest and the gas release is greatest.

[0043] Based on this mechanism, the present invention adopts a segmented temperature control process in the adhesive removal stage: the temperature is raised at an extremely slow rate of 0.2-0.5℃ / min in the main decomposition temperature range of the adhesive (250-400℃), and at least one heat preservation platform is set in this temperature range (preferably at 300℃ and / or 380℃), and the heat preservation time is 1-4h.

[0044] The reason for this process design is that the "zipper-unzipping" decomposition of PPC is a process of gradual breaking of molecular chains, and each decomposition stage requires a certain amount of time to be fully completed. If the heating rate is too fast, the decomposition gases will be released in a concentrated manner in a short period of time, which may not only create high pressure inside the particles leading to cracking, but may also cause carbon deposits to form on the particle surface due to insufficient gas escape. The extremely slow heating rate and long-term heat preservation platform allow each decomposition stage to be fully completed, and the decomposition products have sufficient time to diffuse out from the inside of the particles through the pore network, avoiding the accumulation of residual carbon on the particle surface.

[0045] In addition, segmented temperature-controlled debinding helps maintain the structural integrity of spherical precursor particles—the slow heating rate controls the speed of organic matter removal, preventing excessively rapid escape from causing defects such as particle cracks, delamination, or peeling.

[0046] Supporting process improvement 2: Pulsed atmosphere disturbance During the desiccant removal and heat preservation platform stage, as the decomposition products diffuse from the inside of the particles to the outside, a gas film may form on the particle surface. The decomposition gas forms a locally high-concentration gas layer near the particle surface, which hinders the further escape of the internal gas.

[0047] To address this issue, this invention introduces pulsed atmospheric disturbance during the glue removal and insulation platform stage: a vacuum-purging-protective gas cycle is performed every 15-45 minutes. The principle behind this operation is as follows: during the vacuum stage, the furnace pressure drops sharply, disrupting the gas film on the particle surface, and the internal gas accelerates its escape under the pressure difference; during the gas filling stage, the rapid influx of protective gas generates an airflow scouring effect, carrying the escaped gaseous products away from the particle surface. Periodically repeating this cycle is equivalent to multiple pumping and scouring operations inside the particles, significantly improving gas removal efficiency.

[0048] This process improvement is an active design targeting the characteristics of PPC decomposition gas release—PPC releases a large amount of gas in the 250-400℃ range, and simply relying on slow heating may not completely prevent surface deposition. Pulsed atmosphere disturbance provides additional exhaust power.

[0049] Supporting process improvement 3: Adding trace amounts of nano-oxides Although PPC can be completely decomposed into CO2 and H2O under an inert atmosphere, in actual industrial production, due to factors such as the purity of the furnace atmosphere, the precision of the heating program, and the particle packing state, there is still a possibility that trace amounts of carbon-containing intermediate products may not be completely decomposed. Studies have shown that in the presence of ceramic powder, PPC decomposition may leave gas-mediated carbon residues on the powder surface.

[0050] To further mitigate this risk, this invention adds 0.5-2% (by weight of binder) of nano-oxide powder (selected from at least one of nano-CeO2 and nano-MnO2) to the slurry. The mechanism of action is as follows: within the main decomposition temperature range of PPC (250-400℃), nano-CeO2 / MnO2 releases active oxygen, oxidizing any carbon-containing intermediates that may be generated in situ to CO2. This measure ensures complete carbon removal at the molecular level.

[0051] Selection of sintering aid system and its supporting processes Selection of sintering aids Existing technologies typically use oxides such as Al2O3 and Y2O3 as sintering aids. Their mechanism of action is to exist as a solid second phase at grain boundaries at high temperatures, inhibiting grain boundary movement and promoting densification through a pinning effect. However, these sintering aids remain permanently at the grain boundaries after sintering, and their thermal conductivity is much lower than that of boron nitride, resulting in significant interfacial thermal resistance.

[0052] This invention fundamentally changes this approach—it selects sintering aids that can be automatically discharged from the system after use. Specifically, it includes two solutions: Option 1: Synergistic system of boron oxide (B2O3) and carbonaceous additives B2O3 forms a low-viscosity liquid phase in the 800-1200℃ range, wetting the edges and grain boundaries of boron nitride sheets and promoting particle rearrangement and densification through a dissolution-reprecipitation mechanism. Building upon this, the present invention further introduces a carbonaceous additive (selected from at least one of carbon black and graphite, added at 5-20% of the mass of B2O3), whose mechanism of action is as follows: in the 1200-1600℃ temperature range, carbon undergoes a carbothermic reduction reaction with B2O3.

[0053] Specifically, in the temperature range of 1250-1300℃, B2O3 is reduced by C to generate the intermediate gaseous product B2O2; when the temperature reaches above 1300℃, B2O2 is further reduced by C to generate B or B4C.

[0054] The boron atoms generated in the reaction can dissolve into the adjacent boron nitride lattice (occupying boron sites), not only avoiding their residue as impurities but also helping to repair boron vacancy defects in the boron nitride crystal structure. The CO / CO2 gas generated in the reaction escapes, further chemically removing B2O3 from the system. Some of the generated B4C reacts with BN at higher temperatures (>1800℃): B4C + 7BN → 4B + 7N2↑, and the generated B also dissolves into the BN lattice.

[0055] The unique advantage of this synergistic system is that it upgrades the physical volatilization of B2O3 to a chemical transformation-volatilization-carbothermic reduction reaction, which converts B2O3 into gaseous products and soluble B atoms, making the removal of B2O3 more thorough. At the same time, the transformation products can also repair the boron nitride lattice.

[0056] Option 2: Borate ester precursors The present invention also provides another embodiment: using a borate ester compound (selected from at least one of trimethyl borate and triethyl borate) as a precursor for the sintering aid, instead of directly adding B2O3 powder.

[0057] Boronate esters can be completely dissolved in the solvent system of slurries, achieving uniform dispersion at the molecular level—while B2O3 powder is difficult to disperse in slurries in such a uniform manner. During the debinding and heating process (200-400℃), boronate esters hydrolyze or thermally decompose in situ to generate B2O3. B(OCH3)3+ 3H2O → B(OH)3+ 3CH3OH 2B(OH)3→ B2O3+ 3H2O↑ The in-situ generated B2O3 is uniformly distributed at the grain boundaries of each boron nitride particle in the form of extremely fine particles (close to the molecular level). The sintering efficiency is much higher than that of externally added B2O3 powder. Therefore, the required amount can be reduced by 30-50%, which correspondingly reduces the total amount of B2O3 that needs to be volatilized and discharged.

[0058] Supporting process improvement 1: Temperature matching between two-step sintering and carbothermic reduction For the synergistic system of B2O3 + carbonaceous additives, the triggering temperature of the carbothermic reduction reaction is crucial. Studies have shown that the carbothermic reduction of B2O3 begins at 1200-1300℃, and the reaction rate accelerates significantly above 1300℃.

[0059] Based on this mechanism, the sintering process of the present invention adopts a two-step sintering process: first, the temperature is raised to 1350-1450℃ at a rate of 4-6℃ / min and held for 1.5-3h (step one), and then the temperature is raised to 1950-2050℃ at a rate of 2-4℃ / min and held for 2-4h (step two).

[0060] The temperature range of the first step (1350-1450℃) precisely covers the rapid progression range of the carbothermic reduction reaction. Holding this temperature for an extended period (1.5-3 hours) allows B2O3 to fully react with the carbonaceous additives, converting most of the B2O3 into gaseous products (CO / CO2) and soluble B atoms. Simultaneously, the liquid phase of B2O3 fully spreads and wets the grain boundaries within this temperature range, promoting particle rearrangement and initial densification.

[0061] The second step, at a high temperature (1950-2050℃), achieves full bridging and densification between the primary boron nitride particles, while further removing residual trace amounts of B2O3 through volatilization.

[0062] Supporting process improvement 2: High-temperature venting and insulation After the second heat preservation step is completed, the present invention continues to be kept at 1950-2050℃ for 20-60 minutes while maintaining protective gas purging.

[0063] The reason for this process setup is that the CO / CO2 gas generated by the carbothermic reduction reaction and the residual B2O3 vapor need to diffuse from the product grain boundaries to the particle surface and then be carried out of the furnace by the carrier gas. This process takes a certain amount of time. If the temperature is lowered immediately after sintering and holding, the vapor pressure of B2O3 will drop sharply as the temperature decreases, and the residual B2O3 will condense at the grain boundaries. Continuing to hold the temperature at the sintering temperature and maintaining gas purging allows B2O3 to enter the gas phase as fully as possible before cooling and be carried out by the carrier gas, achieving "zero residue".

[0064] Supporting process improvement 3: Synergistic effect of borate ester precursor decomposition and debinding process When borate ester precursors are used, their in-situ hydrolysis to generate B2O3 occurs during the debinding and heating stage (200-400℃), which coincides with the main decomposition temperature range of PPC adhesives. Therefore, while the adhesive decomposes and interconnected pores form inside the particles, the borate ester precursor simultaneously decomposes to generate B2O3. At this time, the generated B2O3 is uniformly distributed at the molecular level on the surface of the newly formed pores and at the grain boundaries, and its dispersion uniformity is far superior to any mechanical mixing method.

[0065] To achieve this synergistic effect, controlling the heating rate during the debinding stage is crucial—if the heating rate is too fast, the borate ester precursor may not have enough time to hydrolyze before being lost due to solvent evaporation; if the heating rate is too slow, production efficiency will be affected. This invention, through the aforementioned segmented temperature-controlled debinding process (heating at 0.2-0.5℃ / min + heat preservation platform), ensures sufficient decomposition of the binder while also providing ample time for the in-situ hydrolysis of the borate ester precursor.

[0066] By selecting specific materials for the binder and sintering aid as described above, and by making corresponding process improvements, this invention achieves near-zero carbon residue and zero sintering aid residue in the final boron nitride particles.

[0067] First, the complete removal of the binder provides a clean grain boundary surface within the particles, which is essential for the sintering aid to function effectively. If the binder decomposes and leaves residual carbon, this carbon will coat the surface of the boron nitride particles and the grain boundaries, hindering the contact and wetting of the B2O3 liquid phase with the boron nitride surface, significantly reducing the sintering aid effect. The residue-free binder of this invention ensures a clean grain boundary surface, allowing the B2O3 liquid phase to fully exert its sintering aid function.

[0068] Secondly, the complete removal of the sintering aid depends on the interconnected pores formed by the decomposition of the binder. Segmented, temperature-controlled binder removal allows the binder to gradually form a network of interconnected particles during decomposition. These pores not only serve as channels for gas escape but also for the subsequent release of B2O3 vapor (or the release of carbothermic reduction products CO / CO2). Without this pore network, the volatilization and release of B2O3 would be significantly hindered.

[0069] Third, the overlap of the decomposition temperatures of the borate ester precursor and the PPC binder achieves dual effects at one temperature. That is, within the same temperature range, both the thermal decomposition of the binder and the in-situ conversion of the sintering aid precursor are completed, simplifying the process and improving efficiency.

[0070] The preparation method of the present invention will be further described in detail below.

[0071] The method for preparing spherical boron nitride particles provided by this invention includes three steps: slurry preparation, spray granulation, and heat treatment. Its core features are: the carbon residue from the thermal decomposition of the binder under an inert atmosphere is less than 0.05 wt%, ensuring no carbon residue after binder removal; and the sintering aid has a volatilization rate greater than 95% at the sintering temperature, ensuring no second phase residue after sintering.

[0072] In embodiments of the present invention, the binder is selected from polypropylene carbonate (PPC) or polyethylene glycol (PEG). The number-average molecular weight of PPC is preferably 50,000-200,000, and the number-average molecular weight of PEG is preferably 10,000-50,000. If the molecular weight is too low, the bonding strength will be insufficient; if the molecular weight is too high, the solubility and dispersibility will decrease.

[0073] Adding 0.5-2% nano CeO2 or MnO2 relative to the binder mass to the slurry is used to release active oxygen in the binder decomposition temperature range, and to oxidize any carbon-containing intermediate products that may be generated in situ into CO2.

[0074] The sintering aid is a mixture of B2O3 and carbonaceous additives (carbon black or graphite), with the amount of carbonaceous additives being 5-20% of the mass of B2O3. The role of the carbonaceous additives is to undergo a carbothermic reduction reaction with B2O3, converting it into gaseous products and soluble boron atoms.

[0075] The sintering aid is a borate ester precursor (trimethyl borate or triethyl borate), which hydrolyzes in situ during the binder removal process to generate B2O3. This method achieves uniform molecular-level dispersion of B2O3, resulting in higher sintering efficiency.

[0076] The adhesive removal process employs a segmented temperature control technique: the temperature is increased extremely slowly at 0.2-0.5℃ / min within the main decomposition temperature range of PPC (250-400℃), and a holding plateau is set at 300℃ and / or 380℃ for 1-4 hours. The extremely slow heating and long holding time ensure that each decomposition stage is fully completed, allowing sufficient time for the decomposition products to diffuse and escape, thus avoiding surface carbon residue.

[0077] During the heat preservation platform stage, a pulsed atmosphere disturbance cycle of vacuuming and protective gas filling is performed every 15-45 minutes. The periodic changes in gas pressure force the decomposition gas out of the particles.

[0078] The sintering process consists of two steps: the first step is to hold at 1350-1450℃ for 1.5-3 hours to trigger the carbothermic reduction reaction, and the second step is to hold at 1950-2050℃ for 2-4 hours to achieve complete densification.

[0079] After the second heat preservation step is completed, continue heat preservation at 1950-2050℃ for 20-60 minutes while maintaining gas purging to allow B2O3 to fully volatilize and be discharged.

[0080] The dispersant is selected from aniline oligomers and polyethyleneimine; the solvent is a mixture of water, isopropanol and ethanol; the process conditions for spray granulation are: inlet temperature 150-190℃, outlet temperature 90-110℃, liquid feed rate 3.5-5.5L / h, and centrifugal atomizing disc motor frequency 120-180Hz.

[0081] The spherical boron nitride particles prepared by the above method have a median particle size D50 of 50-120 μm, a carbon residue of less than 0.01 wt%, and no second phase residue at the grain boundaries.

[0082] To provide a clearer understanding of the technical content of this invention, the following embodiments are provided for detailed description. Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods. Unless otherwise specified, the raw materials involved in the following embodiments are all commercially available products that can be purchased from the market or prepared using existing methods.

[0083] The above-described technical features of the present invention and the technical features specifically described below (such as in the embodiments) can be combined with each other to form new or preferred technical solutions.

[0084] Example 1 Raw material preparation: Hexagonal boron nitride (purity ≥99%, median particle size D50 = 3μm). The binder is polypropylene carbonate (PPC, QPAC). ® 40. Number average molecular weight 100,000). The dispersant is polyethyleneimine (PEI, number average molecular weight 10,000). The sintering aid is a mixture of boron oxide (B2O3, purity ≥98%) and carbon black, with the carbon black added at 10% of the mass of B2O3. The solvent is a mixture of water, isopropanol, and ethanol in a volume ratio of 4.5:9.1:86.3. In addition, 1% nano-CeO2 powder relative to the mass of PPC is added.

[0085] Step S1: Slurry Preparation Hexagonal boron nitride powder, PPC binder, PEI dispersant, sintering aid (B2O3 + carbon black), nano CeO2, and solvent were prepared according to the mass ratio of boron nitride: binder: dispersant: sintering aid: nano CeO2: solvent = 10:0.3:0.27:0.63:0.003:25. After mixing in a stirred tank at 1900 rpm for 2 hours, the pH was adjusted to 7 with ammonia or dilute nitric acid to stabilize the slurry.

[0086] Step S2: Spray granulation The slurry obtained in step S1 is fed into a spray granulation tower via a peristaltic pump for spray drying. The feed rate is 4.8 L / h, the inlet temperature is 180℃, the outlet temperature is 100℃, and the centrifugal atomizing disc motor frequency is set to 150 Hz. After centrifugation and drying, spherical precursor particles are obtained.

[0087] Step S3: Heat treatment The spherical precursor particles obtained by spray granulation are transferred to a crucible and placed in a sintering furnace.

[0088] (1) Degreasing: A segmented temperature-controlled adhesive removal process was adopted. Under a nitrogen atmosphere, the temperature was increased from room temperature to 300℃ at a rate of 0.3℃ / min and held for 2 hours; then increased from 300℃ to 380℃ at a rate of 0.3℃ / min and held for 2 hours; finally, the temperature was increased from 380℃ to 550℃ at a rate of 0.5℃ / min. During the holding plateau stages at 300℃ and 380℃, a pulsed atmosphere disturbance cycle of vacuuming and nitrogen purging was performed every 30 minutes (vacuuming to 100Pa followed by nitrogen purging to atmospheric pressure, repeated 3 times).

[0089] (2) Sintering: After debinding, the furnace cavity was evacuated to 80 Pa, and then high-purity nitrogen (≥99.999% purity) was introduced to purge the furnace cavity, repeating this process three times. A two-step sintering process was adopted: the temperature was increased from room temperature to 1400℃ at a rate of 5℃ / min and held for 2 hours (carbothermic reduction reaction stage); then the temperature was increased to 2000℃ at a rate of 3℃ / min and held for 3 hours (complete densification stage). After holding at 2000℃, the temperature was maintained at 2000℃ for another 30 minutes while nitrogen purging continued. After the holding period, the furnace was cooled to room temperature to obtain spherical boron nitride particles.

[0090] Performance characterization: such as Figure 1 As shown, the obtained spherical boron nitride particles exhibit good sphericity and retain their complete morphology. Figure 2 As shown, the XRD pattern reveals a pure hexagonal boron nitride phase with no B4C or other impurity phase diffraction peaks. Carbon content analysis (oxygen-nitrogen analyzer) shows a carbon residue of <0.01 wt%. The median particle size D50 is approximately 75 μm.

[0091] Take 30 parts of the above-mentioned spherical boron nitride, 60 parts of thermally conductive composite powder (alumina, zinc oxide, etc., D50=5μm), and 30 parts of silicone oil, and stir under vacuum for 5 minutes to obtain a thermally conductive gel. The thermal conductivity was tested using a Xiangyi DRL-V thermal conductivity meter, and the result was 7.4 W / m·K.

[0092] Example 2 The difference from Example 1 is that in step S1, the binder is polyethylene glycol (PEG, number average molecular weight 20,000), replacing PPC. Other process parameters are the same as in Example 1.

[0093] The obtained spherical boron nitride particles have a D50 of 74 μm. XRD analysis showed no impurity phases, a carbon residue of <0.01 wt%, and no second phase residue at the grain boundaries. The thermally conductive gel has a thermal conductivity of 7.1 W / m·K.

[0094] Example 3 The difference from Example 1 is that in step S1, the sintering aid is triethyl borate (replacing B2O3 + carbon black), and the amount added is 0.3% of the mass of boron nitride. Triethyl borate hydrolyzes in situ to generate B2O3 during the debinding and heating process. Other process parameters are the same as in Example 1.

[0095] The obtained spherical boron nitride particles had a D50 of 76 μm, and XRD analysis showed no impurity phases, a carbon residue of <0.01 wt%, and no second phase residue at the grain boundaries. The thermally conductive gel had a thermal conductivity of 7.3 W / m·K.

[0096] Example 4 The difference from Example 1 is that nano-CeO2 is not added in step S1. Other process parameters are the same as in Example 1.

[0097] The obtained spherical boron nitride particles had a D50 of 75 μm, and XRD analysis showed no impurity phases. The carbon residue was approximately 0.02 wt%, slightly higher than in Example 1 but still much lower than in the traditional PVB system. The thermal conductivity of the thermally conductive gel was 7.0 W / m·K.

[0098] Example 5 The difference from Example 1 is that in step S3, the heating rate for glue removal is 0.5℃ / min, and the temperature is maintained at 300℃ for 1 hour and 380℃ for 1 hour. Other process parameters are the same as in Example 1.

[0099] The obtained spherical boron nitride particles had a D50 of 76 μm, and XRD analysis showed no impurity phases, with a carbon residue of approximately 0.015 wt%. The thermal conductivity of the thermally conductive gel was 6.9 W / m·K.

[0100] Example 6 The difference from Example 1 is that pulsed atmosphere disturbance is not used in step S3. Other process parameters are the same as in Example 1.

[0101] The obtained spherical boron nitride particles have a D50 of 75 μm, and XRD analysis shows no impurity phases, with a carbon residue of approximately 0.018 wt%. The thermal conductivity of the thermally conductive gel is 6.8 W / m·K.

[0102] Example 7 The difference from Example 1 is that in step S3, sintering is performed using a one-step process (directly increasing the temperature to 2000℃ at 5℃ / min and holding for 5 hours), instead of two-step sintering. Other process parameters are the same as in Example 1.

[0103] The obtained spherical boron nitride particles had a D50 of 75 μm, and XRD analysis revealed trace amounts of B4C impurity phase (due to insufficient carbothermic reduction reaction time). The thermal conductivity of the thermally conductive gel was 6.2 W / m·K.

[0104] Example 8 The difference from Example 1 is that in step S3, after the 2000℃ heat preservation is completed, the 30-minute heat release and heat preservation are not performed; the temperature is lowered directly. Other process parameters are the same as in Example 1.

[0105] The obtained spherical boron nitride particles had a D50 of 76 μm, and XRD analysis showed trace amounts of B2O3 residue at the grain boundaries. The thermal conductivity of the thermally conductive gel was 6.4 W / m·K.

[0106] Comparative Example 1 The difference from Example 1 is that in step S1, the binder is polyvinyl butyral (PVB) instead of PPC; and nano CeO2 is not added. Other process parameters are the same as in Example 1.

[0107] The resulting spherical boron nitride particles have a D50 of 76 μm, such as Figure 3 As shown, XRD reveals a distinct B4C impurity phase. The thermal conductivity of the thermally conductive gel is 5.2 W / m·K.

[0108] Comparative Example 2 The difference from Example 1 is that in step S1, the sintering aid is a mixture of Al2O3 and Y2O3 (mass ratio 3:1), replacing B2O3 + carbon black. Other process parameters are the same as in Example 1.

[0109] The resulting spherical boron nitride particles have a D50 of 77 μm, such as Figure 4 As shown, XRD reveals residual Al / Y oxide second phase at the grain boundaries. The thermally conductive gel has a thermal conductivity of 5.5 W / m·K.

[0110] Comparative Example 3 The difference from Example 1 is that in step S1, the binder is PVB (replacing PPC), the sintering aid is Al2O3+Y2O3 (replacing B2O3+carbon black), and nano CeO2 is not added. Other process parameters are the same as in Example 1.

[0111] The obtained spherical boron nitride particles had a D50 of 76 μm. XRD analysis revealed a distinct B4C impurity phase and residual Al / Y oxide second phase at the grain boundaries. The thermally conductive gel had a thermal conductivity of 4.8 W / m·K.

[0112] The results of the above embodiments and comparative examples are shown in Table 1 below.

[0113] Table 1 As shown in Table 1, it can be seen from Example 1 and Comparative Example 1 that by using PPC instead of traditional PVB as a binder, the carbon residue content was reduced from >0.1% to <0.01%, the B4C impurity phase was completely eliminated, and the thermal conductivity was improved by about 42%.

[0114] As can be seen from Example 1 and Comparative Example 2, when the synergistic system of B2O3 + carbonaceous additives is used to replace the traditional Al2O3 + Y2O3 as a sintering aid, there is no second phase residue at the grain boundaries, and the thermal conductivity is improved by about 35%.

[0115] As can be seen from Example 1 and Comparative Example 3, the thermal conductivity of the "double zero residue" design (PPC+B2O3+C) is increased from 4.8W / m·K to 7.4W / m·K compared with the traditional solution (PVB+Al2O3+Y2O3), which is an increase of 54%, fully demonstrating the effectiveness of the technical solution of the present invention.

[0116] As can be seen from Examples 1 and 4, the addition of nano CeO2 further reduced the carbon residue (from 0.02% to <0.01%), verifying its chemical preservation effect.

[0117] As can be seen from Examples 1 and 5-6, the heating rate and holding time of segmented temperature-controlled glue dispensing, as well as pulsed atmosphere disturbance, are all important factors affecting carbon residue. Optimizing these supporting process parameters can further reduce carbon residue.

[0118] As can be seen from Examples 1 and 7-8, the two-step sintering process (providing sufficient temperature and time window for the carbothermic reduction reaction) and high-temperature venting and heat preservation (allowing B2O3 to fully volatilize and be discharged) are both key supporting processes for achieving zero residue of sintering aids.

[0119] In summary, this invention utilizes polypropylene carbonate or polyethylene glycol, which can be completely decomposed under an inert atmosphere, as a binder. It combines this with a synergistic system of boron oxide and carbonaceous additives or borate ester precursors as sintering aids. Furthermore, it incorporates optimized processes such as segmented temperature-controlled binder removal, nano-oxide addition, pulsed atmosphere disturbance, two-step sintering, and high-temperature venting and heat preservation, all tailored to the physicochemical properties of these raw materials. This achieves a near-zero residue effect, with no carbon residue in the binder (<0.01wt%) and no second-phase residue in the sintering aids. The resulting spherical boron nitride particles exhibit pure grain boundaries and a complete crystal structure. When combined with thermally conductive compound powder and silicone oil, the thermal conductivity reaches 7.4 W / m·K, an improvement of over 54% compared to traditional processes. This allows for wide application in high-end thermal management fields such as thermal interface materials, thermally conductive gels, and thermally conductive pads.

[0120] Finally, it should be emphasized that the above are merely preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention can have various changes and modifications. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing spherical boron nitride particles, characterized in that, The preparation method includes the following steps: Step S1: Mix hexagonal boron nitride powder, binder, dispersant, sintering aid and solvent to prepare slurry; Step S2: The slurry is dried and shaped by spray granulation to obtain spherical precursor particles; Step S3: The spherical precursor particles are debinded and sintered to obtain spherical boron nitride particles; The adhesive is selected from at least one of polypropylene carbonate and polyethylene glycol. The sintering aid is a mixture of boron oxide and carbonaceous additives or a borate ester compound. The carbonaceous additive is selected from at least one of carbon black and graphite, and the borate ester compound is selected from at least one of trimethyl borate and triethyl borate. In step S1, the slurry also contains 0.5-2% nano-oxide powder relative to the mass of the binder, wherein the nano-oxide is selected from at least one of nano CeO2 and nano MnO2.

2. The preparation method according to claim 1, characterized in that, In step S1, the sintering aid is a mixture of boron oxide and the carbonaceous additive, and the amount of the carbonaceous additive added is 5-20% of the mass of boron oxide.

3. The preparation method according to claim 1, characterized in that, In step S1, the sintering aid is the borate ester compound.

4. The preparation method according to claim 1, characterized in that, In step S3, the adhesive removal adopts a segmented temperature-controlled adhesive removal process: the temperature is increased at a rate of 0.2-0.5℃ / min in the main decomposition temperature range of the adhesive, and at least one heat preservation platform is set in the main decomposition temperature range, and the heat preservation time of the heat preservation platform is 1-4h.

5. The preparation method according to claim 4, characterized in that, During the glue removal process, at the insulation platform stage, a vacuuming and protective gas filling operation is performed every 15-45 minutes.

6. The preparation method according to claim 1, characterized in that, In step S3, the sintering adopts a two-step sintering process: first, the temperature is raised to 1350-1450℃ at a rate of 4-6℃ / min and held for 1.5-3h, and then raised to 1950-2050℃ at a rate of 2-4℃ / min and held for 2-4h.

7. The preparation method according to claim 6, characterized in that, After the second holding step of sintering is completed, continue holding at 1950-2050℃ for 20-60 minutes while maintaining protective gas purging.

8. The preparation method according to claim 1, characterized in that, In step S2, the process conditions for spray granulation are: inlet temperature 150-190℃, outlet temperature 90-110℃, liquid inlet rate 3.5-5.5L / h, and centrifugal atomizing disc motor frequency 120-180Hz.

9. A spherical boron nitride particle, characterized in that, The spherical boron nitride particles are prepared by the preparation method according to any one of claims 1-8.